2016
DOI: 10.18632/oncotarget.13940
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-17 is downregulated in esophageal adenocarcinoma cancer stem-like cells and promotes a radioresistant phenotype

Abstract: Resistance to neoadjuvant chemoradiation therapy (CRT) remains a critical barrier to the effective treatment of esophageal adenocarcinoma (EAC). Cancer stem-like cells (CSCs) are a distinct subpopulation of cells implicated in the resistance of tumors to anti-cancer therapy. However, their role in the resistance of EAC to CRT is largely unknown. In this study, using a novel in vitro isogenic model of radioresistant EAC, we demonstrate that radioresistant EAC cells have enhanced tumorigenicity in vivo, increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 59 publications
(76 reference statements)
1
46
0
Order By: Relevance
“…Subsequently, numerous studies demonstrated that miRNAs serve important roles in various carcinomas (22)(23)(24)(25)(26). In addition, Polioudakis et al (27) reported that miRNAs are located at 50% of all fragile regions or sites presenting copy number alterations in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, numerous studies demonstrated that miRNAs serve important roles in various carcinomas (22)(23)(24)(25)(26). In addition, Polioudakis et al (27) reported that miRNAs are located at 50% of all fragile regions or sites presenting copy number alterations in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…miR-17-5p suppresses C6orf120 expression to decrease CSCs chemo-and radioresistance. Therefore, miR-17-5p could be a biomarker for CSC resistance evaluation during EAC treatment [151].…”
Section: Mir-17-5pmentioning
confidence: 99%
“…Until recently, some progresses were obtained in the eld of neoadjuvant radiotherapy resistance. For example, MiR-17-5p has been reported to signi cantly enhance the sensitivity of X-rays to radioresistant cells as well as downregulate and promote antiradioactive phenotypes in esophageal adenocarcinoma cancer stem-like cells [3]. Overexpression of TCN1 is reportedly associated with adverse treatment responses and outcomes in rectal cancer patients receiving concurrent neoadjuvant chemoradiotherapy, indicating the potential prognostic value of this gene [4].…”
Section: Introductionmentioning
confidence: 99%